Process of Quality Control of Bottled Water at PT. Tirta Purbalingga Adijaya, Bogor - Elsa Yuliani; Nur Wijayanti (Indonesian Journal of Food Technology, 2023)
Quality control is important in the drinking water production process. Drinking water sourced from nature, of course, contains a variety of minerals, ions, and even microorganisms, so it needs to be processed first so that it meets the needs of the human body and is safe for consumption. PT. Tirta Purbalingga Adijaya, Bogor in producing bottled drinking water refers to SNI 3553: 2015 concerning requirements for drinking water quality, as well as in processing it refers to the Regulation of the Minister of Health No.32 of 2017 concerning Standards for Quality Standards for Environmental Health and Water Health Requirements for Sanitation Hygiene Purposes , Swimming Pools, Solus Per Aqua, And Public Baths. PT. Tirta Purbalingga Adijaya, Bogor implements the Hazard Analysis Critical Control Point (HACCP) system where both raw water, processing and finished products are quality controlled every hour by water treatment operators and the results are verified by Quality Control analysts. Important things that become critical control points are filtering with carbon filters and ozone injection. If these two things are not controlled, it will affect the quality content of the drinking water produced and cause hazards such as residual chlorine and microbial contamination so that the product does not meet standards and cannot be marketed. The tests carried out were physical tests such as organoleptic tests, chemical tests such as chlorine content, ozone, metals and others as well as microbiological tests such as total microbes, fungi, coliform and pseudomonas aeruginosa. Based on the analysis that was carried out for 1 week on January 9-14 2023, it was concluded that the Prim-A brand bottled drinking water produced by PT. Tirta Purbalingga Adijaya, Bogor has met the standards set in Indonesia and is safe for human consumption.